Serological Investigation of Newcastle Disease in Selected Districts of Buno Bedelle Zone, Ethiopia - Mamo T (Dove Medical Press, 2021)
Tamirat Mamo,1 Lama Yimer2 1Seyo District Livestock Development Office, Dembi Dollo, Ethiopia; 2School of Veterinary Medicine, Wollega University, Nekemte, EthiopiaCorrespondence: Lama YimerSchool of Veterinary Medicine, Wollega University, Nekemte, EthiopiaTel +251 917081237Email lemayimer@gmail.comPurpose: Newcastle disease causes considerable loss in the poultry industry worldwide and its outbreaks are regularly reported from all continents of the world, including Ethiopia. The investigation was conducted from October 2020 to June 2021 to determine the prevalence of Newcastle disease (ND) in districts selected from Buno Bedele zone, Western Oromia.Methods: The study design used was a cross-sectional type. For this study, a total of 480 serum samples were collected as per sample collection guideline from randomly selected chickens that were apparently healthy and had no history of vaccination against Newcastle disease. Indirect ELISA was performed and all data were analyzed using SPSS statistical software.Results: From serological investigation, overall seroprevalence of Newcastle disease was 30%. Seroprevalence of Newcastle disease was 34.94%, 22.22%, and 31.76% in Didessa, Chora, and Gachi districts, respectively. Among computed risk factors, breed showed statistically significant difference and the odds of infection were lower in adult than in young chickens. Similarly, the odds of infection with Newcastle disease virus were significantly higher in crossbred than in locally bred backyard chickens.Conclusion: This study revealed Newcastle disease was prevalent in the study areas; therefore, regular investigation of Newcastle disease should be conducted along with detailed studies on molecular characterization of circulating field strains in the area.Keywords: Buno Bedele, Ethiopia, indirect ELISA, Newcastle disease